IMF Staff papers : Volume 26 No. 3. (IMF Staff Papers; IMF Staff Papers, 1979)
This paper examines two questions: What basket of currencies should a small developing country use as the exchange rate standard for its currency? When are discretionary changes of the value of its currency against the standard warranted? The exchange rate policy of a small, price-taking country cannot influence the terms-of-trade fluctuations imposed upon it by deviations from purchasing power parity (PPP) among trading partner countries. The paper introduces two types of calculations that are helpful in analysing the questions raised and employs Indian data to illustrate their use. While sustained differences in financial policies between a country and its trading partners, leading to different rates of inflation, might require a nominal exchange rate adjustment to restore a tenable real rate, structural changes in an economy will often require that the real exchange rate itself adjust toward a new equilibrium. By thus identifying the separate sources of real exchange rate variations, the paper sheds light on the question of whether a change in the exchange rate standard could reduce the variance of the real exchange rate.